Interferensi Bahasa Sunda dalam Tuturan Bahasa Indonesia Masyarakat Kampung Cileutik - Suci Rengganis; Retty Isnendes (Departement of Mathematics Education, 2024)
This study was conducted considering that bilingual people are prone to making mistakes or confusion in using B1 structures into B2 or vice versa which causes confusion in the language structure used. Ambiguity or interference is a bad language attitude so it should not be allowed to be protracted. In conducting this research, the researcher used descriptive analysis method with data collection techniques in the form of observation and interview. The results of this study show that interference still occurs frequently, especially in the lexical field in the form of the inclusion of respondents' Sundanese vocabulary into Indonesian speech. The factors causing the interference are due to the lack of vocabulary mastery of Indonesian (B2) and habits that are carried out in speech. This cannot be avoided by bilingual communities, but it can be minimized by fostering awareness of good language in accordance with the language structure.